The Impact of Opioid Epidemic Trends on Hospitalised Inflammatory Bowel Disease Patients. (7th May 2018) - Cohen-Mekelburg, Shirley; Rosenblatt, Russell; Gold, Stephanie; Burakoff, Robert; Waljee, Akbar K; Saini, Sameer; Schackman, Bruce R; Scherl, Ellen; Crawford, Carl
Abstract: Background and Aims: Opioid use disorder [OUD] has become a public health crisis among patients with chronic disease. Inflammatory bowel disease [IBD] patients are at high risk for OUD because they suffer from chronic relapsing-remitting pain. We aimed to describe the prevalence and trends in OUD-related diagnoses among hospitalised IBD patients. Methods: A retrospective study was performed using weighted Nationwide Inpatient Sample data from 2005 to 2014. Adult IBD hospital visits and OUD-related diagnoses were identified using a previously published schema. Annual diagnoses were calculated. Characteristics associated with OUD were assessed using multivariable logistic regression. Associations between OUD and length of stay were assessed overall and separately for surgical and non-surgical stays. Results: In all, 2.2% of 2585174 weighted discharges with any diagnosis of IBD also had an OUD-related diagnosis, with an 8.8% average annual increase. In multivariable analysis, Crohn's disease, public payer or no insurance, and psychiatric comorbidities were associated with a higher likelihood of OUD, whereas a primary diagnosis of an IBD-related complication was associated with a lower likelihood. An OUD-related diagnosis was associated with 0.84 days (95% confidence interval [CI] 0.71, 0.97] increased length of stay overall, 2.79 days [95% CI 1.44, 4.14] for surgical stays, and 0.71 days [95% CI 0.59, 0.82] for non-surgical stays. Conclusions: OUD-related diagnoses are increasing among IBD patients and are associated with increased length of stay. With a rising prevalence, it is important to screen and diagnose OUD in IBD and refer patients for evidence-based treatment to address unmet patient needs and reduce health care utilisation.